Gaya Hidup Elit Politik Dalam Perspektif Al Qur-an - Khodijah, Miftakhu Nuril; Mufid, Miftara Ainul; Mahmud, Amir; Rohtih, Wiwin Ainis (IAIN KENDARI, 2026)
This study analyzes the concept of political elite lifestyles from the perspective of the Qur’an through a comparative interpretative approach toward Tafsir Ibn Kathir, Tafsir Al-Azhar by Hamka, and Tafsir Al-Misbah by M. Quraish Shihab. The research employs a qualitative method based on library research by examining QS. Al-A’raf [7]: 31, QS. Al-Isra’ [17]: 26–29, QS. Al-Furqan [25]: 67, and QS. Luqman [31]: 18–19. The findings reveal that the three exegetes equally reject israf (excessiveness), tabdzir (wastefulness), and takabbur (arrogance) as deviations from leadership ethics, although they differ in their interpretative approaches. Ibn Kathir emphasizes a normative-textual approach, Hamka highlights social criticism toward consumerism and social inequality, while Quraish Shihab develops the dimensions of public ethics and responsibility in the exercise of power. The novelty of this study lies in its effort to connect Qur’anic interpretation with the phenomenon of modern political elite lifestyles through the perspective of Islamic political ethics. This study affirms that the values of moderation, social justice, and humility remain relevant as moral foundations of leadership in contemporary political contexts.